Transforming the care of atrial fibrillation with mobile health - Turakhia, Mintu P. (J Interv Card Electrophysiol, 2016)
Atrial fibrillation (AF) is a multifaceted and highly variable disease that is often difficult to manage within the traditional health-care model. The conventional model of regular or pre-scheduled appointments with physicians or allied health professionals is poorly suited to the unpredictable and often urgent clinical needs of patients with AF. Mobile health (mHealth) has the potential to dramatically transform the delivery and quality of AF care. In this brief review, we summarize the current limitations and evidence gaps in treating patients with AF. We then describe the current mHealth landscape, changes in telehealth coverage and reimbursement, and recent technological advances of smartphones, mobile applications, and connected wearable devices. We also describe important barriers and challenges, such as clinical management of large volumes of data, application of predictive analytics/machine learning, and the need for high-quality randomized clinical trials.